Penerimaan dan Penyaluran Sarana dan Prasarana di SMAN Mumbulsari Jember - Abdullah adhar, Faris Hilmi Aditiya; Diah Nanda Khoirun Nisak; Bima Andriano Lanove; Haidar Rafli; Rofiq Hidayat (Jurnal Mahasiswa Manajemen, 2025)
Background - The availability of educational facilities and infrastructure is an important foundation in ensuring the quality of teaching and learning services in schools. Amidst the challenges of facility inequality between urban and rural areas, effective management is a vital aspect. SMAN Mumbulsari Jember is a concrete example where educational logistics management plays a central role in supporting the learning process. This is where the urgency of this study lies: how the process of receiving and distributing goods is carried out, and how obstacles and supporting factors influence the effectiveness of such management. Objectives - This study aims to thoroughly analyze the dynamics of receiving and distributing educational facilities and infrastructure at SMAN Mumbulsari. The primary objective is to analyze the extent to which administrative procedures and distribution mechanisms are implemented effectively, as well as to identify supporting and hindering factors. Additionally, this study is expected to formulate relevant strategies to improve the educational logistics management system at the school. Design / Methodology / Approach - This study employs a descriptive qualitative approach using the case study method. Data collection techniques were conducted triangulatively, namely through direct observation in the field, semi-structured interviews with various related parties, and review of internal school documentation. This strategy allows researchers to reconstruct the receipt and distribution process comprehensively and contextually in accordance with the reality at SMAN Mumbulsari.  Findings - The research results indicate that the receipt of facilities and infrastructure has followed administrative standards, such as strict document and goods inspections. However, the distribution of goods faces several challenges, such as mismatches between goods and requests and a lack of technical training for managers. Support from the school principal and a responsive management team serves as a strengthening factor, while limited budgets and procurement delays are the main obstacles. Nevertheless, during the 2022–2025 period, no significant obstacles were identified thanks to effective coordination. Research Implications - These findings highlight the importance of enhancing managerial capacity in educational logistics. Other schools can use SMAN Mumbulsari’s experience as a replicable management model, provided that regular evaluations and staff training remain priorities. Another practical implication is the importance of partnerships with third parties to ensure transparency and accountability in every procurement and distribution process for educational goods. Research Limitations - This study is limited by its scope, which only covers one educational institution, SMAN Mumbulsari, so generalizing the results to other schools requires caution. Additionally, the qualitative approach used emphasizes depth over breadth, so quantitative dimensions such as cost efficiency or distribution speed have not been systematically measured. Keywords: Reception, Distribution, Facilities, Infrastructure, Educational Management